(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Guidance can serve as a second parent of the student whom they can trust. A guidance counselor plays an important role because he/she should understand children’s feelings and emotions that they are keeping for a long time and be good and reliable in assisting with the students’ concerns. Thus, this research was conducted to ensure efficiency and productivity in the guidance department of Bestlink College of the Philippines. The processes that should be improved include ACAEX scholarship, counseling service, Students’ Individual Inventory service, and follow-up service. The qualitative method was utilized in this feasibility study. Based on the observation, several procedures and services of the guidance department should be improved. In ACAEX services, the researchers include decision-making in the submission of requirements to determine whether the requirements submitted by the student are complete or not. For the Students’ Individual Inventory service, freshmen, upperclassmen, and transferees should be separated to avoid delay. In terms of the counseling service, students with referrals and those who are walk-in should be separated to provide better services. In terms of the follow-up service, cumulative form checking and follow-up counseling should be included to improve the workflow. This study aimed to make the flow of each process fast and smooth, without major problems. This study also aimed to provide solutions to the current problems of the guidance department to become more productive and effective.